Bordetella pertussis: new concepts in pathogenesis and treatment - Carbonetti, Nicholas H. (Curr Opin Infect Dis, 2016)
PURPOSE OF REVIEW: The purpose of this review is to summarize and discuss recent findings and selected topics of interest in Bordetella pertussis virulence and pathogenesis and treatment of pertussis. It is not intended to cover issues on immune responses to B. pertussis infection or problems with currently used pertussis vaccines. RECENT FINDINGS: Studies on the activities of various B. pertussis virulence factors include the immunomodulatory activities of filamentous hemagglutinin, fimbriae, and adenylate cyclase toxin. Recently emerging B. pertussis strains show evidence of genetic selection for vaccine escape mutants, with changes in vaccine antigen-expressing genes, some of which may have increased the virulence of this pathogen. Severe and fatal pertussis in young infants continues to be a problem, with several studies highlighting predictors of fatality, including the extreme leukocytosis associated with this infection. Treatments for pertussis are extremely limited, though early antibiotic intervention may be beneficial. Neutralizing pertussis toxin activity may be an effective strategy, as well as targeting two host proteins, pendrin and sphingosine-1-phosphate receptors, as novel potential therapeutic interventions. SUMMARY: Pertussis is reemerging as a major public health problem and continued basic research is revealing information on bacterial virulence and disease pathogenesis, as well as potential novel strategies for vaccination and targets for therapeutic intervention.